Immunity of honeybee guards reflects their transition from house bees to foragers. Issue 3 (3rd May 2020) - Cappa, Federico; Petrocelli, Iacopo; Cini, Alessandro; Pepiciello, Irene; Giovannini, Michele; Lazzeri, AnnaMarta; Perito, Brunella; Turillazzi, Stefano; Cervo, Rita
Abstract : Eusocial insect colonies represent some of the most extreme examples of specialized division of labor. Ageing in workers is often associated with a temporal polyethism in the tasks performed both inside and outside the colony. Such behavioral transition is sometimes linked to a gradual reduction in individual immunity. Here, we studied the immune ability of Apis mellifera guard bees, which represent an intermediate stage between house bees working inside the nest and foragers collecting resources outside, to assess if their specific task is associated with an immune specialization. Through immune challenge with Gram-negative bacteria Escherichia coli, we compared the guards ability to clear bacterial cells from their haemolymph with respect to house bees and foragers. Our findings demonstrate that guards do not show an immune specialization linked to their task but seem to represent a transition also in terms of immunity, since their anti-bacterial response appears intermediate between house bees and foragers.